Advanced materials in automotive engineering - Rowe, Jason (Woodhead Publishing in materials., 2012)
The automotive industry is under constant pressure to design vehicles capable of meeting increasingly demanding challenges such as improved fuel economy, enhanced safety and effective emission control. Drawing on the knowledge of leading experts, Advanced materials in automotive engineering explores the development, potential and impact of using such materials. Beginning with a comprehensive introduction to advanced materials for vehicle lightweighting and automotive applications, Advanced materials in automotive engineering goes on to consider nanostructured steel for automotive body structures, aluminium sheet and high pressure die-cast aluminium alloys for automotive applications, magnesium alloys for lightweight powertrains and automotive bodies, and polymer and composite moulding technologies. The final chapters then consider a range of design and manufacturing issues that need to be addressed when working with advanced materials, including the design of advanced automotive body structures and closures, technologies for reducing noise, vibration and harshness, joining systems, and the recycling of automotive materials. With its distinguished editor and international team of contributors, Advanced materials in automotive engineering is an invaluable guide for all those involved in the engineering, design or analysis of motor vehicle bodies and components, as well as all students of automotive design and engineering. Explores the development, potential and impact of using advanced materials for improved fuel economy, enhanced safety and effective mission control in the automotive industryProvides a comprehensive introduction to advanced materials for vehicle lightweighting and automotive applicationsCovers a range of design ideas and manufacturing issues that arise when working with advanced materials, including technologies for reducing noise, vibration and harshness, and the recycling of automotive materials.